Device and method for treating carbon tetrachloride in underground water by virtue of solar heating aeration method - LIANG ZHI; LIANG XIAO (2016)
The invention discloses a device and method for treating carbon tetrachloride in underground water by virtue of a solar heating aeration method. The device comprises a water inlet pipe, solar heat collecting pipes, a reaction bucket, an aeration device, a water outlet pipe, a residue discharging device, a mud discharging pipe and a control system. According to the method, to-be-treated underground water uniformly enters the solar heat collecting pipes through the water inlet pipe, is heated by the solar heat collecting pipes and enters the reaction bucket through one side of the reaction bucket, air is introduced into the bottom of the reaction bucket by virtue of the aeration device to generate hybrid reaction with to-be-treated underground water at the bottom of the reaction bucket, after the reaction, clean water and floating residue rise in the reaction bucket, finally, clean water is discharged through the water outlet pipe, and the floating residue is discharged through the residue discharging device. A